Efficient leaching process of rare earth, alkali and alkaline earth metals from phosphogypsum based on methanesulfonic acid (MSA) as green & eco-friendly lixiviant. Issue 47 (26th October 2022) - Ait Brahim, Jamal; Merroune, Amal; Boulif, Rachid; Mounir, El Mahdi; Beniazza, Redouane
Abstract : Development of green and eco-friendly leaching process of rare earth elements from phosphogypsum using methanesulfonic acid (MSA). A kinetics investigation was carried out to describe the leaching mechanisms of REEs. Abstract : The leaching of rare earth elements (REEs) from secondary resources is exponentially increasing to supply the widespread range of high-tech applications of these elements including phosphors lighting materials, catalysis and permanent magnets. Phosphate fertilizer byproducts including phosphogypsum (PG) were identified as a potential alternative resource of REEs, not only to face the expansion of market demand, but also to achieve a sustainable management of REE resources. This study reports the leaching of REEs from PG using methanesulfonic acid (MSA) as a green organo-sulfonic acid in comparison with other acids such as p -toluenesulfonic acid (PTSA) and hydrochloric acid (HCl). MSA achieved the highest leaching efficiency of 78% with low solubility of PG under the operating conditions of 3 M, solid to liquid ratio (S/L) of 1/8, 120 min and 25 °C. The optimized leaching process was also modeled using shrinking core theory to assess the kinetics behavior of the system and to enable the determination of the predominant mechanisms. It was demonstrated that the leaching is governed by a product layer diffusion-controlled model with an activation energy of 2.73 kJ mol −1 . The cleaned PG after leaching could greatly meet the quality requirements of the building materials industry.